Optical and X-ray observational search for the possible supernova remnant candidates in the nearby galaxy NGC 1569 - Ercan, E. N.; Aktekin, E.; Cesur, N.; Tumer, A. (OXFORD UNIV PRESS, 2018)
We report the results of our investigation on the possible existence of supernova remnants (SNRs) in the nearby galaxy, NGC 1569, using the CCD imaging and spectroscopic observations from the RTT150 telescope of TUG-TUBITAK in Antalya, Turkey, for two different observing periods. Using [S II]/H alpha >= 0.4 standard criteria, the identification of 13 new SNR candidates for this galaxy is proposed for two different epochs. We found the [S II]/H alpha ratios ranging from 0.46 to 0.84 and H alpha intensities ranging from (2.2 to 32) x 10(-15)erg cm (-2) s (-1 ). [S II]lambda lambda 6716/6731 average flux ratio is calculated from the optical spectra for only one possible SNR candidate. By using this ratio the electron density, N-e , is estimated to be 121 +/- 17 cm(-3), and by using the [O III] lambda 5007/H beta ratio of the same spectrum the shock wave velocity, V-s, is estimated to be in the range 100 < V-s < 150 km s (-1) . Using Chandra data, we find that out of 13 SNR candidates only 10 of them have yielded a spectrum with good statistics, confirming the existence of 10 SNR candidates with matched positions in X-ray region as well. We measure the 0.5-2 keV band flux down to 0.58 x 10(-15) erg cm(-2) s(-1 )for 10 X-ray sources. Our spectral analysis revealed that spectra of the SNR candidates are best modelled with the collisional ionization equilibrium plasma with a temperature range of 0.84 < kT(e) < 1.36 keV.
Keywords: ISM: supernova remnants; galaxies: individual: NGC 1569; galaxies: star formation; X-rays: galaxies; X-rays: ISM; STARBURSTING DWARF GALAXIES; STAR-FORMATION; INTERSTELLAR-MEDIUM; ROSAT OBSERVATIONS; EXTINCTION; DIAGNOSTICS; ABUNDANCES; NEBULAE; MODELS; IONS; Astronomy & Astrophysics